Percaya Listrik Paringin; Program Edukatif Re-Instalasi Cahaya Listrik Paringin - syarif, izuddin (Jurnal Guru Dikmen dan Diksus, 2021)
As a vocational school, the learning system should combine the technical competencies and interpersonal skills of students. For electricity engineering students, the work field is service-oriented. The condition of the Covid-19 pandemic, which made face-to-face learning directed in online mode, was deemed inappropriate for practical use of vocational school students. Through Percaya Listrik Paringin Program, students in grade XI of the Electrical Power Installation Engineering at SMKN 1 Paringin are formed in teams of 2-3 people whose domicile is close together under the guidance of grade XII. The team will work on a lighting installation project in his neighborhood. The final assessment of the project is divided into 2, namely competence and customer satisfaction. All face-to-face activities are limited and replaced by information technology. 22 teams were formed to target 22 houses with 45 light points and 22 sockets points. All activities were carried out from March - May 2020. The program gave 100% results the team was declared to have completed the competency assessment. While customers are satisfied with a mean score of 4.85. The economic impact that is felt is the practicum material that schools no longer need to pay for and free installation services for customers.